Cytomegalovirus in pediatric systemic lupus erythematosus: prevalence and clinical manifestations. (June 2015) - Rozenblyum, E V; Levy, D M; Allen, U; Harvey, E; Hebert, D; Silverman, E D
Cytomegalovirus (CMV) is a beta-herpesvirus and antibodies to this virus are common in patients with systemic lupus erythematosus (SLE). However, few studies have examined the relationship between CMV infection and SLE. Objectives: Our objectives were: 1) to determine the prevalence of CMV infection at the time of SLE diagnosis, and 2) to determine the risk factors for CMV infection. Methods: A database review of 670 patients with pediatric SLE (pSLE) seen over a 20-year period identified seven patients with a CMV infection detected at the time of diagnosis of SLE. CMV was diagnosed by serology, urine and bronchoalveolar lavage. Clinical manifestations, laboratory findings, virology studies and treatments were reviewed. Results: CMV infection was detected in seven patients at the time of SLE diagnosis (1.04% of total cohort): six were female: mean age was 13 years. Predominant features included non-Caucasian ethnicity ( p < 0.01 as compared to total SLE cohort), persistent fevers on prednisone in seven and nephrotic syndrome in four. Laboratory findings included: anemia in seven, lymphopenia in five, elevated liver enzymes in four, with anti-dsDNA and anti-RNP antibodies present in six and five, respectively. Six patients received ganciclovir and CMV hyperimmune globulin (Cytogam®) with the continuation of prednisone during CMV treatment. Six of seven fully recovered without sequelae (one without treatment) but one patient died with active CMV infection. Conclusions: There were 1.04% of patients with pSLE who developed CMV infection. All were of non-Caucasian ethnicity. Persistent fever despite prednisone, with concomitant anemia, may be additional clues to CMV infection in pSLE. We suggest all patients have routine testing for CMV immunity at initial presentation of pSLE.